DINAMIKA AKAD DALAM TRANSAKSI EKONOMI SYARIAH - Rahmawati, Rahmawati (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2011)
Transaction is one of law product (sharia and jurisprudence) that has a lot of development in accordance to human dynamics of the classical period to the present day. In the future, it will always envolve to follow the dynamics of economic system by maintaining the substance in the middle of economical global contentions. Transaction becomes one of Islamic and sharias (revelation) product law to ensure human walfare. As a norm, transactions in Islamic finance or Islamic economics can be fused into the world economic system. This can be a filtering and balancing for the economical system that runs stable towards the benefit of all parties.DOI: 10.15408/aiq.v3i1.2494